Uji Stabilitas Mikrobiologis Pembersih Gigi Tiruan dengan Bahan Minyak Atsiri Kulit Batang Kayu Manis (Cinnamomum burmannii) - Niken Pristianingrum; Soebagio Soebagio; Elly Munadziroh (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2012)
Denture cleaners are products designed to clean stains, deposits, and debris from the surface of the denture, by soaking or brushing with tooth brush and toothpaste for dentures. Cinnamon is a tree with aromatic bark has a very strong odor. Cinnamon has the effect of antifungal, antiviral, bactericidal, and larvasidal. The aim of this research made denture cleaning preparations with ingredients of essential oil of cinnamon bark and microbiological stability test to be have done. In this research, microbiological stability test that includes total plate count test and pathogen microbial test denture cleaning with ingredients of essential oil cinnamon bark 2%, which is stored in a period of 1 week, 2 weeks, 3 weeks, 4 weeks, 2 months, and 3 months. In addition to supporting the results of the study, researchers conducted a preliminary test of the effectiveness of essentials oil of cinnamon bark against Candida albicans. Showed that there was no change in total plate count and the growth of microbial pathogens in denture cleaning preparations with the ingredients of essential oil of cinnamon bark up to 3 months. This shows that the stocks stable in storage at room temperature until the 3 months. Denture cleaning preparations was stable in storage up to 3 months. weeks